N-Iodosuccinimide-Mediated Oxidative Coupling of Indoles and Phenols: A Synthetic Study toward the Benzofuroindoline Moiety of Bipleiophylline - Denizot, Natacha; Guillot, Régis; Kouklovsky, Cyrille; Vincent, Guillaume (Synthesis, 2018)
We report our efforts to apply an N-iodosuccinimide-mediated dearomative oxidative coupling of indoles and phenols to benzofuroindoline-containing polycyclic scaffolds related to the natural product bipleiophylline. Suitable conditions from N-substituted indoles are developed and applied to the synthesis of a hexacyclic model starting from a tetracyclic ABCE precursor.
Keywords: oxidative coupling; indole; dearomatization; phenol; benzofuroindoline; bipleiophylline